2017
DOI: 10.1016/j.idairyj.2016.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Role of pH in the recovery of bovine milk oligosaccharides from colostrum whey permeate by nanofiltration

Abstract: Milk oligosaccharides are associated with improved health outcomes in infants. Nanofiltration (NF) is used for isolation of bovine milk oligosaccharides (BMO). The study aim was to improve the recovery of BMO from lactose-hydrolyzed colostrum whey permeate. The retention factors of carbohydrates at various pH and transmembrane pressures were determined for a nanofiltration membrane, which was used at pilot scale to purify BMO. Carbohydrates were quantified by liquid chromatography and characterized using nano-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 28 publications
1
31
0
Order By: Relevance
“…WP and HWP samples were diluted 10 to 1000 times and filtered through a 0.2-μm membrane. For monosaccharide analysis, a 25-uL aliquot was injected into a Carbo-Pac PA10 (Dionex, Sunnyvale, CA, USA) column at 1.2 mL/min flow rate as described previously [ 22 ]. The nitrogen in the spent media and biomass was quantified using the Dumas combustion method (AOAC 990.03) (vario Max cube; Elementar Americas Inc., Ronkonkoma, NY, USA).…”
Section: Methodsmentioning
confidence: 99%
“…WP and HWP samples were diluted 10 to 1000 times and filtered through a 0.2-μm membrane. For monosaccharide analysis, a 25-uL aliquot was injected into a Carbo-Pac PA10 (Dionex, Sunnyvale, CA, USA) column at 1.2 mL/min flow rate as described previously [ 22 ]. The nitrogen in the spent media and biomass was quantified using the Dumas combustion method (AOAC 990.03) (vario Max cube; Elementar Americas Inc., Ronkonkoma, NY, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Whey permeate, a low-value by-product obtained after whey proteins have been recovered, contains BMOs and has the potential to serve as a raw material for large-scale oligosaccharide isolation (Dallas et al 2014, Zivkovic & Barile 2011). Membrane filtration can be used to recover oligosaccharides present in whey permeate (Cohen et al 2017, de Moura Bell et al 2016), making these compounds more readily available as a functional food ingredient. Such oligosaccharides recovered from dairy streams could serve as ingredients for infant formula, as their composition is similar to that of HMOs and such an ensemble cannot currently be produced synthetically (Meli et al 2014, Simeoni et al 2016).…”
Section: Bovine Milk Oligosaccharides: Structures and Compositionmentioning
confidence: 99%
“…As mentioned earlier, bovine dairy streams are another promising source for larger-scale isolation of milk oligosaccharides (Barile et al 2009, Cohen et al 2017). A recent clinical study showed that consumption of BMOs by adult volunteers was remarkably well-tolerated, even at dosages of up to 35% of daily fiber intake (Smilowitz et al 2017).…”
Section: Diets Supplemented With Exogenous Milk Oligosaccharidesmentioning
confidence: 99%
“…The prebiotic function of OS is theorized to provide human milk with the key ability to selectively modulate the gut microbiota of infants [ 8 ], and these compounds are believed to make a significant contribution to healthy infant development. The health benefits associated with milk OS have begun to motivate development of large-scale recovery techniques for the dairy industry, which would allow more widespread consumption of the typically underutilized OS in processing streams [ 9 , 10 ]. Growing interest in milk OS, their in vivo functions, and opportunities for their utilization has created a need for efficient detection, characterization and quantification strategies.…”
Section: Introductionmentioning
confidence: 99%